Going Against the Grain in an Urban Arizona High School: Secondary Preservice Teachers Emerging as Culturally Responsive Educators. (2nd January 2016) - Ramirez, Pablo; Jimenez-Silva, Margarita; Boozer, April; Clark, Ben
Abstract: This one year study examines the journey of two preservice urban high-school teachers in Arizona as they enact Culturally Responsive Teaching in a year-long student teaching residency. Factors that influenced their Culturally Responsive Teaching practices are discussed along themes that emerged from interviews and classroom observations. Recommendations for ways of integrating Culturally Responsive Teaching in teacher education programs are provided.